Tinjauan Komprehensif tentang Nilai-Nilai Sosio-Emosional dalam Surah Al- Ma'un: Kontribusinya terhadap Kesejahteraan Psikologis Siswa Muslim - Hamidah, Nurlaela; Purnomo, Halim; Nashori, Fuad; Somantri, Ace (Bayani, 2025)
This literature review aims to examine the contribution of social and emotional values ??contained in Surah Al-Ma'un and their contribution to the psychological well-being of Muslim students. This study examines various relevant literature to identify key themes related to social values ??such as caring for others, sharing, and social justice, as well as emotional values ??such as empathy, patience, and self-control. Through a literature review, this article examines various studies relevant to the topic. The method used is Library Research through various scientific journal databases on Google Scholar, tafsir books, and other scientific literature sources with clear inclusion and exclusion criteria to ensure the relevance and quality of the selected literature. The results of the review indicate a positive relationship between the understanding and practice of the social-emotional values ??of Surah Al-Ma'un (such as caring, sharing, and self-control) with the improvement of students' psychological well-being. These findings suggest that the values ??of Surah Al-Ma'un can be an important foundation in building students' emotional intelligence and psychological well-being. The conclusion of this study is that integrating the values ??of Surah Al-Ma'un into students' daily lives, particularly in educational and social contexts, has the potential to improve their quality of life and psychological well-being.